A scaffold merging approach to Hsp90 C-terminal inhibition: synthesis and evaluation of a chimeric library12. Issue 3 (30th January 2017) - Davis, Rachel E.; Zhang, Zheng; Blagg, Brian S. J.
Abstract : Two previously identified Hsp90 C-terminal inhibitors were merged into a single scaffold that manifested improved Hsp90 inhibitory activity. Abstract : Inhibition of the Hsp90 C-terminus is an attractive therapeutic paradigm for the treatment of cancer, however the developmental space of C-terminal inhibitors is limited. It was hypothesized that the combination of two previously identified scaffolds into a single structure could provide a platform for which to probe the three-dimensional space within the Hsp90 C-terminal binding pocket. The resulting chimeric compounds displayed anti-proliferative activity at low micromolar concentrations and manifested inhibitory activity in an Hsp90-dependent rematuration assay. Initial structure–activity relationships suggest that this new scaffold binds Hsp90 in a conformation different from that of the parent compounds, and consequently, provides a new opportunity to develop more efficacious inhibitors of the Hsp90 C-terminal binding pocket.